1996
DOI: 10.1007/bf00408642
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac phosphocreatine deficiency induced by GPA during postnatal development in rat

Abstract: The effect of chronic administration of beta-guanidinopropionic acid (GPA) on the protein profiling, energy metabolism and right ventricular (RV) function was studied in the rat heart during the weaning and adolescence period. GPA was given in tap water (1-1.5%) using pair drink controls. The feeding of animals with GPA solution for a six week period resulted in elevation of heart to body weight ratio due to body growth retardation. GPA accumulated in the myocardium up to 67.37 +/- 5.3 mumoles.g dry weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Total myocardial CK activity was not significantly changed (10.1% (SD 14.0)) after βGPA (Figure 4) [30], [35], [46], [52], [55], [74], [90]. In line with this, the cytoplasmatic isoforms CK-MM, CK-MB, and CK-BB remained unchanged in vivo, but changed in vitro by resp.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Total myocardial CK activity was not significantly changed (10.1% (SD 14.0)) after βGPA (Figure 4) [30], [35], [46], [52], [55], [74], [90]. In line with this, the cytoplasmatic isoforms CK-MM, CK-MB, and CK-BB remained unchanged in vivo, but changed in vitro by resp.…”
Section: Resultssupporting
confidence: 58%
“…21.0% and 55.0% in type I and type II fiber predominant muscle of rats and plasma free fatty acid concentration by 66.7% after βGPA [31]. In contrast, 2 other studies reported unchanged fasting plasma concentrations of fatty acids, triglycerides, and total lipids in rats, but numerical details were not provided [30], [56].…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations